Application of MtSNP marker for genetic identification of forensically important sarcophagid flies (Diptera: Sarcophagidae) in China. (December 2015) - Zhang, C.Q.; Fu, X.L.; Yang, X.; Liu, J.S.; Guo, Y.D.
Abstract: The species identification of forensically important sarcophagid flies (Diptera: Sarcophagidae) is very difficult and requires strong taxonomic expertise. More and more methods according to the mitochondrial DNA (MtDNA) and nuclear fragments are raised, but the current methods of molecular identification have some defects, such as insufficient discrimination power, high cost, time-consuming and so on. In this study, the CO II sequences of sarcophagid flies were analyzed to establish the SNP-based genotyping system for the first time. Using this system by PSQ, we can identify the species of forensically important Sarcophgid flies with high discrimination power at a low cost in the short time. The SNPs marker system shows a new idea for genetic identification of forensic insects.